(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Multiple Sclerosis (MS) is a progressive neurodegenerative disease characterized by demyelination and plaque formation and having manifestations in multiple systems of the body. Signs and symptoms depend on the site of lesion. Prevalence of MS is estimated to be 2.8 million cases worldwide, the mean age being 20 to 40 mostly affecting females. Genetic factors also contribute greatly. Considering the etiological factors, pathogenesis and symptoms it can be correlated to different types of Avarana. A cluster of symptoms seen in different types of Avarana can be observed here. Along with Avarana the treatment principles of Jwara, Vatavyadhi, Vatashonita, Manasika vyadhis can also be adopted in this condition at different stages. The present work is a case report of a 22 year old male diagnosed with MS and treated effectively. This work is done in an effort to understand MS in terms of the basic principles of Ayurveda and to discuss the effectiveness of Ayurvedic treatment protocol in MS.